An Analysis of Grammatical Errors in Writing The Procedure Text of The Ninth Grade of SMP Negeri 5 Botomuzoi in 2022/2023 - Veronika Nurdelima Mendrofa; Adieli Laoli (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This research is aimed to investigate the errors made by the ninth grade of SMP Negeri 5 Botomuzoi in writing procedure text. It intends to (1) identify the types of errors done by the students in writing procedure text, and (2) find the causes of the errors. It applied a qualitative research. The participants were 20 students of ninth grade of SMP Negeri 5 Botomuzoi. The data were the procedure text written by the students. Those described the types of errors. Then questionnaires got from the english teacher and students described the cause of errors. Results of the data analysis indicated that there were 182 frequencies of errors done by 20 students. The types of erros done by students were omission, addition, misinformation and misordering. The frequencies of omission type done by students were 48 (26.37%). The frequencies of addition done by students were 32 (17.58%). The frequencies of misinformation done by students were 66 (36,26%). The frequencies of misordering done by students were 36 (19.78%). These errors are caused the lack of target language knowledge (intralingual errors). They consisted of lack of vocabulary, spelling, the use of plural and making noun phrases. The second cause was the frist language or mother tongue (interlingual errors). There the errors caused by the influence of first language.